Studi greci e latini per Giuseppina Matino - Ferruccio, Conti Bizzarro (Fuori Collana, 2020)
This volume contains twenty-nine essays on Greek and Latin texts, presented to the renowned Hellenist Giuseppina Matino by members of the 'Sciences of Antiquity' Unit at the Department of Humanities of the University Federico II in Naples. The papers range from Greek language and literature to Latin language and literature, classical philology, papyrology, humanistic Latin literature, Byzantine philology, and classical reception. Such a variety of subjects reflects the multiple research fields that are being pursued at the 'Sciences of Antiquity' Unit, of which Giuseppina Matino has been in charge during the latest years of her academic career.